Editorial Introduction - Catherine F. Compton-Lilly (Networks: An Online Journal for Teacher Research, 2011)
The Spring 2011 issue of Networks offers a rich variety of articles to our readers. Touching on technology, movement in classrooms and multicultural competence the three lead articles ask educator to both consider instructional practices of the future and to reflect on the cultural knowledge that we do and do not bring to classrooms. In all three articles, readers are asked to rethink some of their assumptions about what happens in classrooms and what we need to consider as we make decisions about classroom practices.